Influence of Participatory Monitoring and Evaluation on Performance of Public Secondary Schools Projects in Mutomo Sub-County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
In schools, participatory monitoring and evaluation is a tool for enhancing performance of projects and improving overall efficiency of project planning, management and implementation. PM&E offers new way for involving the stakeholders in planning and implementation of projects in public schools environment. The purpose of the study was to establish influence of participatory monitoring and evaluation on performance of public schools projects in Mutomo Sub-County, Kenya. The population involves 33 public secondary schools which forms the target population of the study. Sampling design which was used in the study is non probability (purposeful sampling). The study collected data by use of questionnaires then descriptive analysis and inferential analysis was used for quantitative data. Data was presented by use of tables, percentages and frequencies, pie charts mean and standard deviations by statistical package (SPSS V17). The study established that stakeholders are not involved in the process of management of school projects. Moreover, established that institutional strengthening can be improved by open forums, meetings and seminars which should involve stakeholders air their views and negotiate their perspectives. The study concluded the following: institutional strengthening has influence on the performance since the stakeholders had little knowledge on participatory monitoring and evaluation and if the objectives will be achieved efforts can be made by the appointing authority to train the selected stakeholders .Negotiations perspectives of shareholders has influence on performance of public schools in the sub county, Public accountability still has influence on the performance of public secondary schools projects, Project planning has influence on performance of public school projects and lastly TSC policy has influence on the performance of public school projects. The study recommends that public secondary should involve the stakeholders in the process of projects management by creating meeting, forums and seminars that will allow them to air their views, needs and opinions which make them negotiate their perspectives and make critical decisions.